Corporate Governance in Emerging Economies: A Review of the Principal–Principal Perspective - Young, Michael N.; Peng, Mike W.; Ahlstrom, David; Bruton, Garry D.; Jiang, Yi (Journal of Management Studies, 2008)
abstract Instead of traditional principal–agent conflicts espoused in most research dealing with developed economies, principal–principal conflicts have been identified as a major concern of corporate governance in emerging economies. Principal–principal conflicts between controlling shareholders and minority shareholders result from concentrated ownership, extensive family ownership and control, business group structures, and weak legal protection of minority shareholders. Such principal–principal conflicts alter the dynamics of the corporate governance process and, in turn, require remedies different from those that deal with principal–agent conflicts. This article reviews and synthesizes recent research from strategy, finance, and economics on principal–principal conflicts with an emphasis on their institutional antecedents and organizational consequences. The resulting integration provides a foundation upon which future research can continue to build.